Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
Vũ Ngọc Anh
Xem chi tiết
✓ ℍɠŞ_ŦƦùM $₦G ✓
27 tháng 6 2017 lúc 8:43

a ) 10 x X - 1 - 3 - 5 - 7 - ... - 19 = 2 + 4 + 6 + ... + 20

10 x X - 1 - 3 - 5 - 7 - ... - 19 = 110

10 x X - ( 1 + 3 + 5 + 7 + ... + 19 ) = 110

10 x X - 100 = 110

10 x X = 110 + 100

10 x X = 210

       X = 210 : 10

       X = 21

khai
27 tháng 6 2017 lúc 8:56

a 10 x X-1-3-5-7-....-19 = 2+4+6+....+20

​10xX-1-3-5-7-....-19=110

​10xX=110+1+3+5+7+....+19

​10xX=210

​X=210:10

​X=21

b là 4

Phương Phương
Xem chi tiết
nthv_.
23 tháng 9 2021 lúc 15:23

4x2 + 3x - 4x2 + 8x - 10 = 0

11x - 10 = 0

x = 10/11

 

Nguyễn Lê Phước Thịnh
23 tháng 9 2021 lúc 15:23

\(3x\left(\dfrac{4}{3}x+1\right)-4x\left(x-2\right)=10\)

\(\Leftrightarrow4x^2+3x-4x^2+8x=10\)

\(\Leftrightarrow x=\dfrac{10}{11}\)

Nguyễn Hoàng Minh
23 tháng 9 2021 lúc 15:23

\(3x\left(\dfrac{4}{3}x+1\right)-4x\left(x-2\right)=10\\ \Leftrightarrow4x^2+3x-4x^2+8x=10\\ \Leftrightarrow11x=10\Leftrightarrow x=\dfrac{10}{11}\)

kira uchiha -.-
Xem chi tiết
Yeutoanhoc
20 tháng 6 2021 lúc 11:01

$ a/ 12x(x – 5) – 3x(4x - 10) = 120$

`<=>12x^2-60x-12x^2+30x=120`

`<=>-30x=120`

`<=>x=-4`

Vậy `x=-4`

$b/ 9x(x + 4) – 5x(3x + 2) = 112 - 2x(3x + 1)$

`<=>9x^2+36x-15x^2-10x=112-6x^2-2x`

`<=>-6x^2+26x=112-6x^2-2x`

`<=>28x=112`

`<=>x=4`

Vậy `x=4`

$c/ 3x(1 – x) - 5x(3x + 7) = 154 + 9x(5 – 2x)$

`<=>3x-3x^2-15x^2-35x=154+45x-18x^2`

`<=>-32x-18x^2=154+45x-18x^2`

`<=>77x=-154`

`<=>x=-2`

Vậy `x=-2`

XiangLin Linh
Xem chi tiết
Nguyễn Lê Phước Thịnh
14 tháng 10 2021 lúc 23:01

a: Ta có: \(x\left(2x-3\right)-\left(2x-1\right)\left(x+5\right)=17\)

\(\Leftrightarrow2x^2-3x-2x^2-10x+x+5=17\)

\(\Leftrightarrow-12x=12\)

hay x=-1

Quang Huy
Xem chi tiết
Thái Viết Nam
9 tháng 9 2016 lúc 21:26

\(0,\left(90\right)\)nhé bạn
 

Die Devil
9 tháng 9 2016 lúc 21:29

\(4x^2+3x-\left(4x^2+8x\right)=10\)

\(4x^2+3x-4x^2-8x=10\)

\(-5x=10\)

\(x=10:\left(-5\right)=-2\)

Huyền Nguyễn
Xem chi tiết
Nguyễn Lê Phước Thịnh
28 tháng 9 2021 lúc 20:39

a: Ta có: \(x^2+3x-10=0\)

\(\Leftrightarrow\left(x+5\right)\left(x-2\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=-5\\x=2\end{matrix}\right.\)

b: Ta có: \(x^2-5x-6=0\)

\(\Leftrightarrow\left(x-6\right)\left(x+1\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=6\\x=-1\end{matrix}\right.\)

hồ trần
Xem chi tiết
l҉o҉n҉g҉ d҉z҉
27 tháng 6 2017 lúc 19:52

Ta có : 9(x + 1)2 - (3x - 2)(3x + 2) = 10

=> 9(x2 + 2x + 1) - (9x2 - 4) = 10

=> 9x+ 18x + 9 - 9x2 + 4 = 10

=> 9x2 - 9x2 + 18x + 13 = 10

=> 18x = 10 - 13

=> 18x = -3 

=> x = \(-\frac{1}{6}\)

hồ trần
Xem chi tiết
l҉o҉n҉g҉ d҉z҉
27 tháng 6 2017 lúc 19:52

Ta có : 9(x + 1)2 - (3x - 2)(3x + 2) = 10

=> 9(x2 + 2x + 1) - (9x2 - 4) = 10

=> 9x+ 18x + 9 - 9x2 + 4 = 10

=> 9x2 - 9x2 + 18x + 13 = 10

=> 18x = 10 - 13

=> 18x = -3 

=> x = \(-\frac{1}{6}\)

nguyễn hữu kim
Xem chi tiết

\(x^3-2x^2+x-2=0\\ \Leftrightarrow x^2\left(x-2\right)+\left(x-2\right)=0\\ \Leftrightarrow\left(x^2+1\right)\left(x-2\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x^2+1=0\\x-2=0\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x^2=-1\left(vô.lí\right)\\x=2\end{matrix}\right.\\ Vậy:x=2\\ ---\\ 2x\left(3x-5\right)=10-6x\\ \Leftrightarrow6x^2-10x-10+6x=0\\ \Leftrightarrow6x^2-4x-10=0\\ \Leftrightarrow6x^2+6x-10x-10=0\\ \Leftrightarrow6x\left(x+1\right)-10\left(x+1\right)=0\\ \Leftrightarrow\left(6x-10\right)\left(x+1\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}6x-10=0\\x+1=0\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=\dfrac{5}{3}\\x=-1\end{matrix}\right.\)

\(4-x=2\left(x-4\right)^2\\ \Leftrightarrow4-x=2\left(x^2-8x+16\right)\\ \Leftrightarrow2x^2-16x+32+x-4=0\\ \Leftrightarrow2x^2-15x+28=0\\ \Leftrightarrow2x^2-8x-7x+28=0\\ \Leftrightarrow2x\left(x-4\right)-7\left(x-4\right)=0\\ \Leftrightarrow\left(2x-7\right)\left(x-4\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}2x-7=0\\x-4=0\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=\dfrac{7}{2}\\x=4\end{matrix}\right.\\ ---\\ 4-6x+x\left(3x-2\right)=0\\ \Leftrightarrow4-6x+3x^2-2x=0\\ \Leftrightarrow3x^2-8x+4=0\\ \Leftrightarrow3x^2-6x-2x+4=0\\ \Leftrightarrow3x\left(x-2\right)-2\left(x-2\right)=0\\ \Leftrightarrow\left(3x-2\right)\left(x-2\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}3x-2=0\\x-2=0\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=\dfrac{2}{3}\\x=2\end{matrix}\right.\)

nghia
Xem chi tiết
Nguyễn Lê Phước Thịnh
21 tháng 7 2023 lúc 10:41

a: =>x^2-25-x^2-3x=10

=>-3x=35

=>x=-35/3

b: =>4x^2-9-4(x^2+4x+4)=5

=>4x^2-9-4x^2-16x-16-5=0

=>-16x-30=0

=>x=-15/8

c: =>9x^2+45x-9x^2+4=7

=>45x=3

=>x=1/15

d: =>x^3+3x^2+3x+1-x^3-3x^2+5x=8

=>8x=7

=>x=7/8